2019
DOI: 10.3390/ijerph16101708
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Young People’s Intention toward Municipal Solid Waste Sorting

Abstract: With the rapid growth of urban economy and population in China, the output of municipal solid waste (MSW) has dramatically increased becoming a constant threat to residents’ living environment and health. The classification intention of residents plays a pivotal role in solving the problem of MSW disposal. While numerous studies have examined the classification behavior of MSW from the perspective of ordinary residents and households, few studies have attempted to understand young people’s sorting intention. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 82 publications
(93 reference statements)
7
54
0
Order By: Relevance
“…However, the notion of ethics and moral can be important determinants for the waste sorting engagement, even if they do not directly respond to the notion of the environment. Young people in China have been shown to sort waste rather because of the moral obligation they feel to act in a certain way along with the perception of the behavioral control and subjective norms rather than attitude or concerns for the environment [86]. A Slovenian study confirmed that the three key aspects in the ethical decision making regarding whether or not to participate in waste sorting are moral recognition, moral judgement and moral intention [87].…”
Section: Dynamics Between Moral Ethics and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the notion of ethics and moral can be important determinants for the waste sorting engagement, even if they do not directly respond to the notion of the environment. Young people in China have been shown to sort waste rather because of the moral obligation they feel to act in a certain way along with the perception of the behavioral control and subjective norms rather than attitude or concerns for the environment [86]. A Slovenian study confirmed that the three key aspects in the ethical decision making regarding whether or not to participate in waste sorting are moral recognition, moral judgement and moral intention [87].…”
Section: Dynamics Between Moral Ethics and Sustainabilitymentioning
confidence: 99%
“…Incentives to sort and the individual waste sorting behavior has been studied among ordinary residents of different countries and areas, as well as in the context of their affluence and other socio-demographical aspects [30,63,86,[90][91][92]. However, none of these studies aimed to understand incentives to engage in waste sorting specifically among immigrants.…”
Section: Incentives To Change Patternsmentioning
confidence: 99%
“…A green attitude is undoubtedly a crucial driver of diverse green intentions/activities contributing to the enhancement of the prediction power of any theoretical framework for such intentions/activities [24][25][26]. Indeed, many empirical studies have provided evidence that attitudes toward an eco-friendly product are positively and significantly linked to pro-environmental purchase intentions toward the product [22,24,25,27]. If customers hold a green attitude that is favorable for a particular green behavior, they are likely to practice it and be willing to accept possible inconveniences related to the behavior [25,27].…”
Section: Green Attitude and Its Functionmentioning
confidence: 99%
“…Indeed, many empirical studies have provided evidence that attitudes toward an eco-friendly product are positively and significantly linked to pro-environmental purchase intentions toward the product [22,24,25,27]. If customers hold a green attitude that is favorable for a particular green behavior, they are likely to practice it and be willing to accept possible inconveniences related to the behavior [25,27].…”
Section: Green Attitude and Its Functionmentioning
confidence: 99%
See 1 more Smart Citation